2014
DOI: 10.1371/journal.pone.0107436
|View full text |Cite
|
Sign up to set email alerts
|

A 35-Year Trend Analysis for Back Pain in Austria: The Role of Obesity

Abstract: BackgroundThe prevalence of back pain is constantly increasing and a public health problem of high priority. In Austria there is a lack of empirical evidence for the development of back pain and its related factors. The present study aims to investigate trends in the prevalence of back pain across different subpopulations (sex, age, obesity).MethodsA secondary data analysis based on five nationally representative cross-sectional health surveys (1973–2007) was carried out. Face-to-face interviews were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…47 Obese men showed the uppermost increase in and greatest risk for back pain. Interestingly, 2 other large European studies, involving 105,841 participants in Norway and the Netherlands, found that the association of higher BMI with back pain was stronger in women.…”
Section: Back and Radicular Painmentioning
confidence: 99%
“…47 Obese men showed the uppermost increase in and greatest risk for back pain. Interestingly, 2 other large European studies, involving 105,841 participants in Norway and the Netherlands, found that the association of higher BMI with back pain was stronger in women.…”
Section: Back and Radicular Painmentioning
confidence: 99%
“…Additionally, in the Austrian Health Interview Survey, 36.1 % of men and 39.2 % of women reported that they had ever been affected by chronic spine complaints [5]. An increase of the prevalence of back pain between 1973 and 2007 from 13.9 to 32.9 % of the adult Austrian population (age standardised) has been reported [6]. However, here limitations due to different survey techniques and different applied questions (e.g.…”
Section: Back Pain Functionality Quality Of Life and Health Satisfmentioning
confidence: 99%
“…Those characteristics/behaviours which were most often considered to impact on treatment outcome (Table 3) included what acupuncture author Bob Flaws once called "the three frees"-relaxation, diet and exercise-but also self-motivation, willingness to follow advice given, general state of health and openness to new experiences. In the HRV literature on acupuncture, parasympathetic activation or an improvement in sympathovagal balance is often found to result from acupuncture treatment [56][57][58], so a pre-existing ability to relax could facilitate this. The remaining items are all quite straightforward and easy to interpret in the context of acupuncture, where for instance patients less open to new experiences are presumably less likely to procure treatment in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…Items shown in bold red type appear in the same deciles both NOW and THEN; those underlined appear in Most "Yes" responses and Least "No" responses (NOW or THEN), or vice versa. (60) Age (59) Sceptical (57) Willing to follow advice (9) Central sensitisn (13) Able to relax (14) Alexithymia (15) Psychotic (15) Self-motivated (15) Ethnicity (73) Gender (68) Education (56) Relnship status (53) Gender issues (50) Age (47) Willing to follow advice (7) Commitment (14) General health (14) Openness (16) Self-motivated (16) Exercise 17DK Alexithymia (78) Gender issues (52) Central sensitsn (51) TCM pattern (47) Child poverty (45) Character when young (44) Willing to follow advice (5) Able to relax (6) Age (6) Negativity 7Gender (7) Self-motivated (8) a gender, character when young, childhood poverty and extraverted/introverted. Two of these also appear under "Fewest responses (THEN)".…”
Section: On Specific Questions Requiring "Yes" or "No" Responsesmentioning
confidence: 99%
See 1 more Smart Citation